2005
DOI: 10.4489/myco.2005.33.1.051
|View full text |Cite
|
Sign up to set email alerts
|

Increased Salinity Tolerance of Cowpea Plants by Dual Inoculation of an Arbuscular Mycorrhizal FungusGlomus clarumand a Nitrogen-fixerAzospirillum brasilense

Abstract: Pot greenhouse experiments were carried out to attempt to increase the salinity tolerance of one of the most popular legume of the world; cowpea; by using dual inoculation of an Am fungus Glomus clarum and a nitrogen-fixer Azospirillum brasilense. The effect of these beneficial microbes, as single- or dual inoculation-treatments, was assessed in sterilized loamy sand soil at five NaCl levels (0.0~7.2 ds/m) in irrigating water. The results of this study revealed that percentage of mycorrhizal infection, plant h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 50 publications
2
16
0
2
Order By: Relevance
“…Cowpea is considered to be highly mycotrophic (Molla & Solaiman, ) which leads to enhancement of below and above ground biomass, nutrients accumulation, protein content and grain yield under different water regimes (Kwapata & Hall, ; Oliveira et al., 2017a; Oruru, Njeru, Pasquet, & Runo, ; Rabie, Aboul‐Nasr, & Al‐Humiany, ). However, our results showed that association between AM fungi and cowpea did not result in increased plant growth or seed yield (Tables and ).…”
Section: Discussionmentioning
confidence: 99%
“…Cowpea is considered to be highly mycotrophic (Molla & Solaiman, ) which leads to enhancement of below and above ground biomass, nutrients accumulation, protein content and grain yield under different water regimes (Kwapata & Hall, ; Oliveira et al., 2017a; Oruru, Njeru, Pasquet, & Runo, ; Rabie, Aboul‐Nasr, & Al‐Humiany, ). However, our results showed that association between AM fungi and cowpea did not result in increased plant growth or seed yield (Tables and ).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to control treatments, dual inoculation of Rhizobium bacteria and mycorrhizal fungi under salt stress, enhanced plant nutrition, growth parameters and proline concentration in Acacia saligna (Soliman et al, 2014), Lathyrus sativus (Jin et al, 2010), Acacia auriculiformis , and Acacia mangium (Diouf et al, 2005). Co-inoculation with Rhizobium and PGPR including Azospirillum brasilense and Pseudomonas species showed the same beneficial effects in Z. mays (Bano and Fatima, 2009), Vigna sinensis (Rabie et al, 2005), and Vicia faba (Rabie and Almadini, 2005), which were more pronounced in plant inoculated with AMF, in addition to Rhizobium and PGPR (Rabie and Almadini, 2005; Rabie et al, 2005). In Cowpea plants, dual inoculation with AMF and nitrogen-fixing bacteria such as A. brasilense increased plant nitrogen content by 230% against 151 and 94% in plants inoculated separately with nitrogen-fixing bacteria and AMF, respectively, at 7.2 dS/m salinity (Rabie et al, 2005).…”
Section: Strategies To Improve Salt Tolerance In Cropsmentioning
confidence: 97%
“…Thus, a screening of both symbiotic partners is necessary for obtaining an efficient N 2 -fixing symbiosis under saline soils (Zahran, 1999). Salinity tolerance of legumes could be better improved by associated Rhizobium with mycorrhizal fungi (Diouf et al, 2005; Jin et al, 2010; Soliman et al, 2014) and/or plant growth promoting rhizobacteria (PGPR; Rabie and Almadini, 2005; Rabie et al, 2005; Bano and Fatima, 2009). Compared to control treatments, dual inoculation of Rhizobium bacteria and mycorrhizal fungi under salt stress, enhanced plant nutrition, growth parameters and proline concentration in Acacia saligna (Soliman et al, 2014), Lathyrus sativus (Jin et al, 2010), Acacia auriculiformis , and Acacia mangium (Diouf et al, 2005).…”
Section: Strategies To Improve Salt Tolerance In Cropsmentioning
confidence: 99%
“…Several studies have proven the inhibitory effect of salt stress on the association of plants with symbiotic bacteria. Salt stress inhibits the growth, nodulation, and nitrogen fixation of several legumes, such as soybean (Glycine max) and common bean (Phaseolus vulgaris) [47,48]. An explanation for reduced legume growth may be that salt stress causes failure of the infection and nodulation processes [49].…”
Section: Fresh Weightmentioning
confidence: 99%